Globalizing People Through International Assignments - Black Stewart J.; Gregersen B. Hal; Mendenhall E. Mark; Stroh K. Linda (Allyn And Bacon, 1999)
This book is written primarily for the executive who must deal with the global economy and the strategic role of people in achieving international competitiveness. Preface, Introduction, The Strategic Roles of Global Assignments, The Process of Making Cross-Cultural Adjustments, Before the Assignment, Selecting: Finding the Right People, Training: Helping People Learn to Do the Right Things, During the Assignment, Adjusting: Developing New Mental Maps and Behaviors, Integrating: Balancing Dual Allegiance, Appraising: Determining If People Are Doing the Right Things, Rewarding: Recognizing People When They Do Things Right, After the Assignment, Repatriating: Helping People Readjust and Perform, Retaining: Utilizing the Experienced Global Manager, Managing the Entire Global Assignment Cycle: Establishing Best Practices, References, Index.